Edukasi Kesehatan Reproduksi Remaja Di Karangtaruna Pendowohardjo - Hastuti, Pri; Ekawati, Desi (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2021)
Adolescence is the initial period of maturity of the reproductive organs in humans or the so-called puberty. Based on previous preliminary studies, adolescents prefer sources of reproductive health information obtained from peers and parents, but if this is not given an explanation from health workers directly it will cause different perceptions from each teenager which can cause gaps. Based on the preliminary study, researchers are interested in doing community service with the title "Adolescent Reproductive Health Education in Karangtaruna Pendowohardjo". The purpose of this research is to increase the knowledge of adolescents about the importance of reproductive health from a physical and psychological perspective. Adolescent Reproductive Health Education Activities at Karangtaruna Pendowohardjo were carried out using counseling and demonstration methods, the media used using teaching aids. The target audience in this community service is Youth, especially Youth Organizations in Pendowohardjo Sewon Bantul with a target number of 48 Youth Youth Organizations. The results of this research are that adolescents gain knowledge and skills regarding Reproductive Health through counseling and demonstrations.